2006
DOI: 10.1002/jcp.20644
|View full text |Cite
|
Sign up to set email alerts
|

The TFG protein, involved in oncogenic rearrangements, interacts with TANK and NEMO, two proteins involved in the NF‐κB pathway

Abstract: TRK-fused gene (TFG) was first identified as a partner of NTRK1 in generating the thyroid TRK-T3 oncogene, and is also involved in oncogenic rearrangements with ALK in anaplastic lymphoma and NOR1 in mixoid chondrosarcoma. The TFG physiological role is still unknown, but the presence of a number of motifs involved in protein interactions suggests that it may function by associating with other proteins. We have recently demonstrated that TFG associates and regulates the activity of the tyrosine phosphatase SHP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 33 publications
2
44
0
1
Order By: Relevance
“…TFG is a signaling protein (Roccato et al 2005;Miranda et al 2006). We included it in our functional study because it strongly and specifically interacted with the C-terminal domain of RBFOX1 and RBFOX2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TFG is a signaling protein (Roccato et al 2005;Miranda et al 2006). We included it in our functional study because it strongly and specifically interacted with the C-terminal domain of RBFOX1 and RBFOX2.…”
Section: Discussionmentioning
confidence: 99%
“…TFG is part of signaltransduction pathways, and interacts with the SH2 domain of SHP-1, a protein-tyrosine phosphatase, whose activity it modulates (Roccato et al 2005). It also interacts with TANK and NEMO, two proteins involved in the NF-kB pathway (Miranda et al 2006). To our knowledge, there was no evidence that TFG can bind RNA or regulate RNA metabolism.…”
Section: Coimmunoprecipitation and Mass Spectrometry Identify Fox-1c mentioning
confidence: 99%
“…While the role of TFG in the regulation of normal cellular function was previously unknown, TFG has been shown to interact with SHP-1 phosphatase and regulate its activity (Roccato et al 2005). Furthermore, TFG enhances the effect of TNF-a, TANK, TNF receptorassociated factor (TRAF) 2, and TRAF6 in inducing NF-kappaB activity (Miranda et al 2006). Interestingly, PGE2-dependent stimulation of cumulus expansion in mice is NF-kappaB dependent (Takahashi et al 2006), implying a potential functional link between NF-kappaB activity and key prostanoid-dependent events during the preovulatory period.…”
Section: Discussionmentioning
confidence: 99%
“…MTSS1 is a sonic hedgehog responsive actin binding protein (Callahan et al 2004) and a functional hedgehog signaling system in murine follicles has been reported (Wijgerde et al 2005, Russell et al 2007. TFG is involved in promoting NF-kappaB activity (Miranda et al 2006), which is potentially related to cumulus expansion in mice (Takahashi et al 2006). RABGAP1 is a GTPase that may have novel functions in the ovary.…”
Section: Gonadotropin Surge Induced Up-regulation Of Gene Expression mentioning
confidence: 99%
“…For instance, hnRNP-K inhibition increases apoptosis in response to cytotoxic agents (80), while hnRNP-AB promotes proliferation and metastasis of pancreatic cancer cells (81). In addition to RBPs, other proteins whose methylation has been demonstrated in this study for the first time (CTF8A and TFG) might also explain the enhanced survival capacity of liver tumor cells (82,83) and how it might be regulated by MTA.…”
Section: Partial Deletion Of Mtap Increases the Sensitivity To Liver mentioning
confidence: 67%